2019
DOI: 10.3390/s19122800
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Computer Vision Syndrome in Health Personnel by Means of Genetic Algorithms and Binary Regression Trees

Abstract: One of the major consequences of the digital revolution has been the increase in the use of electronic devices in health services. Despite their remarkable advantages, though, the use of computers and other visual display terminals for a prolonged time may have negative effects on vision, leading to a greater risk of Computer Vision Syndrome (CVS) among their users. In this study, the importance of ocular and visual symptoms related to CVS was evaluated, and the factors associated with CVS were studied, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
0
14
0
7
Order By: Relevance
“…The CVS‐Q © has good psychometric properties derived from the Rasch Analysis, with sensitivity and specificity values of 75.0% and 70.2%, respectively. This questionnaire has been used in Spanish workers 20‐23 and its translation, cultural adaptation and validation into different languages are also being carried out 24…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CVS‐Q © has good psychometric properties derived from the Rasch Analysis, with sensitivity and specificity values of 75.0% and 70.2%, respectively. This questionnaire has been used in Spanish workers 20‐23 and its translation, cultural adaptation and validation into different languages are also being carried out 24…”
Section: Introductionmentioning
confidence: 99%
“…The CVS-Q © has good psychometric properties derived from the Rasch Analysis, with sensitivity and specificity values of 75.0% and 70.2%, respectively. This questionnaire has been used in Spanish workers [20][21][22][23] and its translation, cultural adaptation and validation into different languages are also being carried out. 24 In the absence of CVS studies in European countries, and particularly in Spain, this study was proposed with the aim of estimating the prevalence of CVS in a sample of Spanish university population and determining its relationship with sociodemographic and optical correction factors and exposure to digital devices.…”
mentioning
confidence: 99%
“…The majority of the students in the current study used DD for more than six hours per day, which has been shown to be one of the risk factors of developing CVS [ 16 - 18 ], especially in contact lens users [ 11 ]. It is of interest to note that a higher percentage of students in this study use DDs for more than six hours compared to students in the region [ 2 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eye symptoms increased with duration of VDU use, and markedly increased with more than six hours of screen use ( P = 0.01). Computer use has increased in healthcare with the growing use of electronic medical records; healthcare workers may experience a high prevalence of computer vision syndrome, with symptoms corresponding to increased screen time 20 .…”
Section: Introductionmentioning
confidence: 99%